Syntactic Complexity and Lexical Accuracy in the Written Production of Finnish EFL Learners : a Quantitative Study of 9th-graders’ and Upper Secondary School Students’ Texts - Ali-Hokka, Nikke (My University, 2019)
This thesis analyzes syntactic complexity and lexical accuracy in the written English production of Finnish EFL learners. The main purpose is to examine the development of these two dimensions of learner language and the relationship between them. While complexity and accuracy in learner language have been studied extensively, to the best of my knowledge, no studies so far have examined syntactic complexity and lexical accuracy together in detail. 64 short essays written by Finnish-speaking 9th-graders (n=29) and upper secondary school students (n=35) were analyzed. The 9th-graders formed one group in the comparison, while the upper secondary students were divided into two groups according to how many courses of English they had completed (0–4 courses, n=18; 5–10 courses, n=17). Syntactic complexity was analyzed with an automatic computer software, TAASSC. The analysis of lexical accuracy, then, consisted of counting and categorizing lexical errors. The relationship between syntactic complexity and lexical accuracy was analyzed by calculating correlations. The most noteworthy result of the syntactic complexity tests is the increase in subordination with higher proficiency. This was implied not only by measures that gauge the use of dependent clauses, but also certain measures of unit length. In the analysis of lexical accuracy, no significant differences between the groups were observed in terms of the overall production of lexical errors. Most of these errors were categorized as misspellings. Furthermore, transparently L1-influenced errors were rare. Finally, the correlation calculations suggest no significant relationship between syntactic complexity and lexical accuracy in these data. While these results may provide valid evidence about the development of syntactic complexity and lexical accuracy in the written production of these learner groups, further evidence is needed to draw conclusions about the relationship between the two dimensions. Thus, similar tests could be conducted with other task types than essay writing and other learner groups.
Keywords: English as a Foreign Language, lexical accuracy, lexical errors, syntactic complexity